Smart Monitoring System Pada Pembudidayaan Jamur Tiram Menggunakan Metode Fuzzy Logic - Basirun, Arif Reza; Anggraini, Violita; Al Kautsar, Muhammad Nurudduja (Jurnal TRINISTIK: Jurnal Teknik Industri, Bisnis Digital, dan Teknik Logistik, 2024)
Mushrooms, which are known as food commodities, when cultivated require temperatures between 22-28°C and humidity of 60-80%. Controlling these two factors is very crucial, especially when weather fluctuations occur throughout the day. As a solution, an artificial intelligence-based system was introduced to regulate temperature and humidity. The "fuzzy control" technique in artificial intelligence is an option because of its flexibility and convenience without involving complex mathematical calculations. The Fuzzy Mamdani method is one approach to "fuzzy control" which allows automatic control of temperature and humidity in mushroom cultivation areas. To apply this method, sensors are needed that can provide data to the fuzzy system. This fuzzy system works in four steps: fuzzification, rule determination, inference, and defuzzification. Based on the results of comparative tests with MATLAB software, there is a correctness level of around 26% in the measurement results.